Effectiveness of the Strengthening Families Programme 10-14 in Poland for the prevention of alcohol and drug misuse: protocol for a randomized controlled trial - Okulicz-Kozaryn Katarzyna; Foxcroft David R (BMC, 2012)
Abstract Background Alcohol and other drug use and misuse is a significant problem amongst Polish youth. The SFP10-14 is a family-based prevention intervention that has positive results in US trials, but questions remain about the generalizability of these results to other countries and settings. Methods/Design A cluster randomized controlled trial in community settings across Poland. Communities will be randomized to a SFP10-14 trial arm or to a control arm. Recruitment and consent of families, and delivery of the SFP10-14, will be undertaken by community workers. The primary outcomes are alcohol and other drug use and misuse. Secondary (or intermediate) outcomes include parenting practices, parent-child relations, and child problem behaviour. Interview-based questionnaires will be administered at baseline, 12 and 24 months. Discussion The trial will provide information about the effectiveness of the SFP10-14 in Poland. Trial registration International Standard Randomised Controlled Trial Number: ISRCTN89673828